Odpowiedzi

  • Użytkownik Zadane
2009-11-19T22:44:22+01:00
2x+1=2-√3x
2x + √3x = 2 - 1
x(2 + √3) = 1 /:(2+√3)
x = 1 /[2+√3]
x = 1*[2-√3] / [(2+√3)*(2-√3)]
x = [2-√3]/[2²-(√3)²]
x = [2-√3]/[4 - 3]
x = [2-√3]/1
x = 2-√3
2009-11-19T22:48:45+01:00
2x+1=2-√3x
2x+√3x=2-1
x(2+√3)=1 |: (2+√3)
x= 1/ (2+√3)

x= 1/ (2+√3) × 2-√3/2-√3= 2-√3/4-3= 2-√3

/ kreska ułamkowa
Najlepsza Odpowiedź!
2009-11-19T22:50:22+01:00
Rozwiąż równanie 2x+1=2-√3x

2x+√3x=2-1
x(2+√3)=1
x=1/(2+√3)
x=(2-√3)/(2+√3)(2-√3)
x=(2-√3)/(4-3)
x=(2-√3)/1
x=2-√3